Regulation of StAR by the N-terminal Domain and Coinduction of SIK1 and TIS11b/Znf36l1 in Single Cells - Lee, Jinwoo; Tong, Tiegang; Duan, Haichuan; Foong, Yee Hoon; Musaitif, Ibrahim; Yamazaki, Takeshi; Jefcoate, Colin (Frontiers in Endocrinology, 2016)
The cholesterol transfer function of StAR is uniquely integrated into adrenal cells, with mRNA translation and PKA phosphorylation occurring at the mitochondrial outer membrane (OMM). The StAR C-terminal cholesterol binding domain (CBD) initiates mitochondrial inter-membrane contacts to rapidly direct cholesterol to Cyp11a1 in the inner membrane (IMM). The conserved StAR N-terminal regulatory domain (NTD) includes a leader sequence targeting the CBD to OMM complexes that initiate cholesterol transfer. Here we show how the NTD functions to enhance CBD activity delivers more efficiently from StAR mRNA in adrenal cells and then how two factors hormonally restrain this process. NTD processing at two conserved sequence sites is selectively affected by StAR PKA phosphorylation. The CBD functions as a receptor to stimulate the OMM/IMM contacts that mediate transfer. The NTD controls the transit time that integrates extra-mitochondrial StAR effects on cholesterol homeostasis with other mitochondrial functions, including ATP generation, inter-organelle fusion and the major permeability transition pore in partnership with other OMM proteins. PKA also rapidly induces two additional StAR modulators: SIK1 and Znf36l1/Tis11b. Induced SIK1 attenuates the activity of CRTC2, a key mediator of StAR transcription and splicing, but only as cAMP levels decline. TIS11b inhibits translation and directs the endonuclease-mediated removal of the 3.5-kb StAR mRNA. Removal of either of these functions individually enhances cAMP-mediated induction of StAR. High-resolution fluorescence in situ hybridization (HR-FISH) of StAR RNA reveals asymmetric transcription at the gene locus and slow RNA splicing that delays mRNA formation, potentially to synchronize with cholesterol import. Adrenal cells may retain slow transcription to integrate with intermembrane NTD activation. HR-FISH resolves individual 3.5-kb StAR mRNA molecules via dual hybridization at the 3’- and 5’ ends and reveals an unexpectedly high frequency of 1:1 pairing with mitochondria marked by the matrix StAR protein. This pairing may be central to translation-coupled cholesterol transfer. Altogether, our results show that adrenal cells exhibit high- efficiency StAR activity that needs to integrate rapid cholesterol transfer with homeostasis and pulsatile hormonal stimulation. StAR NBD, the extended 3.5kb mRNA, SIK1, and Tis11b play important roles.